ANALISIS KEPUASAN KONSUMEN BETON READY MIX TERHADAP KUALITAS PELAYANAN PT. SARANA BETON PERKASA - Jawat, I Wayan; Sutarja, I N.; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014DO - 10.24843/SPEKTRAN.2014.v02.i02.p08)
The study about consumers satisfactions toward ready mix concrete company efforts becomes a central topic in construction in Bali. More over, each of ready mix company promotes its comittment consistency in quality and is product services. The aim of these study is to identify the factors which are influenced the services quality towards the consumer satisfaction of ready mix concrete and to know the consumers satisfactions towards services quality. This study used consumers satisfaction survey through sampling technique ( questionnaires distributions to 40 respondent ) by filling  or marking the statements provided. To measure the consumers satisfaction toward the service quality, Importance – Perfomance Analysis was used. The aim is to measure the relation between consumer perseption and product/services quality improvement. The result of questionnaires data analyzes, could be concluded that the services quality was very important but the company didn’t do it maximal.The services included : the on time product delivery, the quick services for the consumers, the trust toward the quality, the consumers quality document, the readyness toward the consumers complaint. While, the services quality which were done well by the company, including : the staff took the mixture sample for the presure test, the staff did the slump test, the consumers got the information about the mixture quality, the slump test is based on the quality requirements, the pressure test is based on the the quality requirements, the concrete pump worked well, the mixer truck worked well, the volume of the mixture is based on the order, and the staff prepared  and used the testing tool on the field.
Keywords: consumer’s satisfactions, services’ quality, Importance – Perfomance Analysis